2013
DOI: 10.1007/s11999-013-3072-x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Hip Center During THA Performed for Protrusio Acetabuli Is Associated With Better Implant Survival

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 19 publications
1
57
0
6
Order By: Relevance
“…32 If the COR does influence these factors, it is mostly because of displacement in the LM plane. 29,30,33 This suggests that in our study only one outlier of 5 mm in the LM plane might be clinically relevant, which appears to have been confirmed as the hip dislocated.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…32 If the COR does influence these factors, it is mostly because of displacement in the LM plane. 29,30,33 This suggests that in our study only one outlier of 5 mm in the LM plane might be clinically relevant, which appears to have been confirmed as the hip dislocated.…”
Section: Discussionsupporting
confidence: 64%
“…Some studies claim that small differences of 1 mm to 2 mm increase wear, the load on the hip, and the risk of aseptic loosening and subsequent revision. [28][29][30] Other studies have found no influence of the COR on wear 31 and good outcomes in patients with a high COR. 32 If the COR does influence these factors, it is mostly because of displacement in the LM plane.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, the center of rotation was lateralized by 6 mm. Baghdadi et al [3] used the same technique to assess the change of the center of rotation and found a mean of 11 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a 3-dimensional templating study, there has been good correlation reported between these methods and fi nal implant position and size of implant used, whether a 2-dimensional or 3-dimensional digital templating method is used. [22][23][24][25][26][27][28][29] With the increasing number of bonepreserving THAs being performed globally, an implant system that optimizes the normal femoral anatomy is benefi cial. This study shows that if the recommended femoral resection level of 5-mm proximal to the shoulder region of the femoral neck is used, the available implant neck angles using a femoral neck-retaining stem are more likely to recreate the 3-dimensional anatomy of the proximal femur.…”
Section: Discussionmentioning
confidence: 99%